Sound transmission behaviour, fire resisting properties as well as structural performance of full scale rubberized lightweight foamed concrete using magnesium oxide board as the skin layer - Ng, Kee Siang (2023)
In Malaysia, the generation of waste tyres is a significant environmental problem, with approximately 8.2 million waste tyres generated annually. To address this issue, this study investigates the potential of rubberized lightweight foamed concrete with the skin layers of magnesium oxide board as a sandwiched wall panel system. First, crumb rubber ground from the waste tyre is incorporated into the concrete mixture at 80 % replacement, producing a fresh density of 1150 kg/m3 . Then, sandwiched wall panels are fabricated from this material by adhesively connecting the rubberized lightweight foamed concrete core to the magnesium oxide board as the skin layers using an adhesive agent. After the fabrication of sandwiched wall panel, four different product and laboratory tests are conducted to evaluate its engineering properties. The Sound Reduction Index (SRI) is determined as 43 dB indicating the ability of the sandwiched wall panel to sound absorption. Besides, the sandwiched wall panel also passes the 2-hour fire resistance rating test and 2.5-minute hose stream test. This essential information indicates the durability of the sandwiched wall panel in adverse conditions such as prolonged exposure to a high-temperature fire scene and the high pressure of the hose stream exerted on it. In addition, the flexural strength test conducted on the sandwiched wall panel also evaluates its Modulus of Rupture (MOR) to meet the standard requirements with a minimum value of 1.5 MPa. The MOR evaluated is 2.2313 MPa for the sandwiched wall panel, and it is fulfilling the standard requirements. In conclusion, this study demonstrates the potential of the rubberized lightweight foamed concrete with the skin layers of magnesium oxide board as a sandwiched wall panel for commercialisation in the construction industry. The engineering properties of the sandwiched wall panel were favourable, with high sound absorption, good fire resistance rating, and sufficient flexural strength, making it suitable for nonload-bearing wall panel applications. Last but not least, this study also contributes to waste tyre management, extends the life cycle of rubber tyres, and promotes sustainable construction practices, namely Industrialised Building System (IBS) and Green Building Index (GBI).